Assessing the Validity of the Qualistar Early Learning Quality Rating and Improvement System as a Tool for Improving Child-Care Quality - Zellman, Gail L. (RAND Corporation, 2008)
As a result of the generally low quality of child care in the United States, quality rating and improvement systems (QRISs) are proliferating in the child-care arena. This study examines the QRIS developed by Qualistar Early Learning, a nonprofit organization based in Colorado, evaluating how reliable the system's components are, whether the QRIS process helped providers to improve, and whether and how much children benefit from such improvement.